2017
DOI: 10.1021/acs.orglett.6b03541
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Rearrangements of Polycyclic α-Ketols

Abstract: It has been proposed that prekinamycin and kinobscurinone may biogenetically isomerize to isoprekinamycin and prefluostatin, respectively, through the corresponding bridgehead α-ketol intermediates. In this transformation, the 6-5 ring system is converted into a 5-6 ring system via an α-ketol rearrangement. In this report, the skeletal rearrangement of polycyclic α-ketols inspired by this hypothetical biosynthetic transformation is reported. In addition, an unexpected rearrangement from dibenzo[b]fluorene to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Remarkably, the 6,7-epoxide group remained unscathed in the reaction. A literature search showed that this mechanistically surprising rearrangement had already been documented in other polycyclic α-hydroxy-β-diketones, suggesting its generality.…”
Section: Resultsmentioning
confidence: 86%
“…Remarkably, the 6,7-epoxide group remained unscathed in the reaction. A literature search showed that this mechanistically surprising rearrangement had already been documented in other polycyclic α-hydroxy-β-diketones, suggesting its generality.…”
Section: Resultsmentioning
confidence: 86%
“…This led us to speculate that 4 is the bonafide product of NzsJ that underwent a spontaneous α-ketol rearrangement reaction (Figure B). Such a rearrangement is also observed in the interconversion from the dibenzo­[ b ]­fluorene skeleton to a benzo­[ g ]­chromene in the synthetic experiments and the biogenetic interconversions between prekinamycin and isoprekinamycin (Figure S17). Density functional theory (DFT) calculations also confirmed that the structure of 4 has a higher energy than that of 5 or 6 (Table S2).…”
mentioning
confidence: 61%
“…The presence of the diazo group in intermediates 78 and 79 is noteworthy in that this functional group has not yet been demonstrated to be compatible with an α-ketol rearrangement. To test the feasibility of their hypothesis, Kawamura et al subjected 80 to basic (Cs 2 CO 3 or K 2 CO 3 ) and acidic (TsOH) conditions [ 27 ]. While TsOH led only to dehydration product 81 , the bases exclusively generated 82 as the result of an α-ketol rearrangement ( Figure 16b ).…”
Section: Reviewmentioning
confidence: 99%